Is the quantity-quality trade-off a trade-off for all, none, or some? - Daniel L. Millimet; Le Wang (Institute for the Study of Labor (IZA), 2009)
Although the theoretical trade-off between the quantity and quality of children is well-established, empirical evidence supporting such a causal relationship - particularly on child health - is limited. We use two measures of child health to asses the quantity-quality trade-off across the entire distribution. Using data from the Indonesia Family Life Survey and controlling for the potential endogeneity of child quantity, we find evidence of a causal trade-off only for some and only in the short-run.
urn:nbn:de:101:1-20090330117
Keywords: C14; D10; I12; O12; 330; Intrahousehold allocation; health; human capital; fertility; quantile treatment effects; stochastic dominance; Kinder; Familienökonomik; Fruchtbarkeit; Haushaltsökonomik; Gesundheit; Bildungsinvestition; Indonesien